Q: 33 plus 27 divided 3 minus 9 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

27 times 3 minus 46 plus 23 equals 58.

X=27

27 divided by 3 equals 9. 27 divided by 9 equals 3.

27/9 = 3 x 2 = 6 + 8 - 3 = 11

16/4-2+5*5 = 27

Related questions

27 times 3 minus 46 plus 23 equals 58.

4188.5

X=27

74

27 divided by 3 equals 9. 27 divided by 9 equals 3.

27/9 = 3 x 2 = 6 + 8 - 3 = 11

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.

16/4-2+5*5 = 27

30

27

27

It is: 27/9 = 3